IMPLEMENTASI PENDIDIKAN MULTIKULTURA DI SD NEGERI 19 SITIUNG - Muhammad Amin; Zulmuqim Zulmuqim; Iswantir Iswantir; Erwin Erwin (JURNAL EDUSCIENCE (JES), 2022)
This research is on the implementation of multicultural education in PAI subjects. This research was conducted at The State Elementary School 19 Sitiung using a descriptive qualitative method. This study aims to determine the extent of the cultivation and application of multicultural education values in the school. From the research results by researchers by conducting observations and interviews with related parties, the importance of multicultural education carries out well. There is no discrimination against minorities and migrants studying and studying at this school—Islamic education values implement as well as possible.